Long Non-Coding RNA GRIK1-AS1 Inhibits the Proliferation and Invasion of Gastric Cancer Cells by Regulating the miR-375/IFIT2 Axis - Zhou, Qi; Li, Yuan; Chen, Lujun; Zheng, Xiao; Jiang, Tianwei; Liu, Juan; Fu, Yuanyuan; Guan, Liping; Ju, Jingfang; Wu, Changping (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) play important roles in various biological processes and human diseases, including cancer. In this study, we demonstrated a regulatory relationship between lncRNA GRIK1-AS1 and miR-375/IFIT2 axis in gastric cancer. Our results show a decreased expression of GRIK1-AS1 in gastric cancer tissues compared to adjacent normal gastric tissues. Gastric cell lines also have reduced levels of GRIK1-AS1 compared to gastric epithelial cell line GES-1. Ectopic expression of GRIK1-AS1 in gastric cancer cell lines significantly inhibits cellular viability, migration, and invasion. RNA-pull down and the luciferase activity assays show that GRIK1-AS1 mainly interacts specifically with miR-375. We further demonstrate a negatively regulatory relationship between lncRNA GRIK1-AS1 and miR-375. We discovered that IFIT2 was one of the direct key downstream target genes of miR-375, and established the important role of the GRIK1-AS1/miR-375/IFIT2 axis in the progression of gastric cancer. Taken together, our results revealed a novel mechanism of GRIK1-AS1 as a sponge to miR-375 that impacts gastric cancer progression via modulating target mRNA IFIT2 translation, and as a result, opens a new strategy to future GRIK1-AS1 based therapeutic development.